Late-onset seizures and epilepsy: Electroclinical features suggestive of autoimmune etiology - Morano, Alessandra; Cerulli Irelli, Emanuele; Salamone, Enrico Michele; Orlando, Biagio; Fanella, Martina; Tinelli, Emanuele; Ruffolo, Gabriele; Zuliani, Luigi; Fattouch, Jinane; Manfredi, Mario; Giallonardo, Anna Teresa; Di Bonaventura, Carlo (Frontiers in Neurology, 2022)
Introduction Late-onset epilepsy (LOE) has recently become a topic of intense research. Besides stroke, tumors, and dementia, autoimmune encephalitis (AE) has emerged as another possible cause of recurrent seizures in the elderly, and may account for a proportion of cases of LOE of unknown origin (LOEUO). This 24-h ambulatory electroencephalography (AEEG)-based study compared patients with LOEUO and AE to identify features suggestive of immune-mediated seizures in the elderly. Materials and methods We retrospectively reviewed 232 AEEG examinations performed in patients over 55 years with ≥6-month follow-up, and selected 21 subjects with AE and 25 subjects with LOEUO. Clinical charts and AEEG recordings were carefully analyzed. Results Twenty-five patients with LOEUO (12 women, mean age at onset 67.9 years) and 21 AE subjects (8 women, mean age at onset 65.7 years) were enrolled. High-frequency seizures were reported in 20/21 AE and 7/25 LOEUO cases (p < 0.00001). Focal aware seizures were more common in AE (14/21 vs. 6/25, p = 0.00058), whereas “isolated” focal-to-bilateral tonic-clonic seizures occurred in 5/25 patients with LOEUO only (p = 0.053). AE subjects reported ictal autonomic manifestations more frequently (p = 0.0033). Three-hundred-seventy and 24 seizures were recorded in 13/21 patients with AE and 3/25 patients with LOEUO, respectively (p = 0.0006). Interictal epileptiform discharges were observed in 70% of both groups, but their sleep activation was more common in AE (p = 0.06). Conclusion Our study shows that high-frequency focal seizures with autonomic manifestations should raise the suspicion of AE in the elderly with new-onset seizures. It also highlights the relevant contribution of AEEG, which might reduce the diagnostic delay and provide useful clues to recognize AE.